Relationship Between Parenting Self Efficacy and Subjective Well Being of Mothers with ADHD Children in Surabaya Indonesia - Yosinaga, Alejo Richie; Subargo, Yopi Lutfi; Baharuddin, Fahyuni (Journal of Social Work and Science Education, 2025)
Every mother wants to provide the best for her child. For mothers of children with Attention-Deficit/Hyperactivity Disorder (ADHD), the daily journey of parenting is often filled with challenges. The purpose of this study was to explore the relationship between Parenting Self-efficacy (PSE) and Subjective Well-Being (SWB) among mothers of ADHD children currently attending Alejo School in Surabaya. This cross-sectional study involved 40 mothers who were selected using purposive sampling technique. Correlation analysis was conducted using Pearson’s product-moment correlation method. SWB was measured using Satisfaction with Life Scale (SWLS) from Diener et al. (1985) and Positive Affect Negative Affect Scale (PANAS) from Watson et al. (1988) while Parenting Self-Efficacy (PSE) was measured using Self Efficacy for Parenting Task Index (SEPTI) from Coleman & Karraker, (2003). The results showed that there was a significant positive relationship between the five aspects of PSE with Satisfaction with Life Scale (r = 0.488 – 0.653, p<.001) and Positive Affect (r = 0.722 – 0.842, p<.001), as well as a significant negative relationship with Negative Affect (r = -0.476 – -0.782, p<.001) of mothers who had ADHD children. This research is expected to provide a deeper understanding of the importance of PSE in influencing the SWB of mothers who have children with ADHD.